Analysis of IoT Use in the Smart Home Context Using the TAM Model: Education and Income as Moderating Variables - Stelamaris, Bonefasia Salvatore; Utomo, Rio Guntur; Yasirandi, Rahmat (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This study aims to develop effective policies and strategies to promote the adoption of IoT technologies, particularly smart home usage in Indonesia, in light of the rapid increase in internet usage and to address the digital divide due to varying education and income levels. Utilizing the Technology Acceptance Model (TAM) and a quantitative methodology, the survey was conducted with 427 smart home users via a digital form distributed on social media. Data was analyzed using TAM variables and additional variables like privacy, compatibility, perceived ease of use, perceived usefulness, attitude towards using, behavioral intention to use, and actual system use, with demographics (income and education) as moderating variables. The results show that privacy, perceived ease of use, and perceived usefulness significantly influence attitudes towards using smart homes, which in turn positively affects users' intention to use them, while compatibility does not. Education and income levels weaken the relationship between external factors and intention to use smart homes. This research highlights the impact of demographic factors on IoT adoption and provides insights for technology providers and policymakers to enhance smart home device adoption in Indonesia.